When the cat's away the mice will play: does regulation at home affect bank risk taking abroad? - Steven Ongena; Alexander Popov; Gregory F. Udell (European Central Bank (ECB), 2012)
This paper provides the first empirical evidence that bank regulation is associated with cross-border spillover effects through the lending activities of large multinational banks. We analyze business lending by 155 banks to 9613 firms in 1976 different localities across 16 countries. We find that lower barriers to entry, tighter restrictions on bank activities, and higher minimum capital requirements in domestic markets are associated with lower bank lending standards abroad. The effects are stronger when banks are less efficiently supervised at home, and are observed to exist independently from the impact of host-country regulation.
Keywords: G21; G28; G32; 330; Bank Regulation; cross-border financial institutions; financial risk; Lending standards